12% VAT increase: Challenges and opportunities for stock investors in Indonesia - Mutahira Nur Insirat; Hasri Ainun Syahfir; Darmawati; Syarifuddin Rasyid (Politeknik Negeri Madiun, 2025)
The increase in Value Added Tax (VAT) from 11% to 12% implemented by the Indonesian government on January 1, 2025 presents both challenges and opportunities for the economy and equity investors. This research explores the impact of the policy on capital market dynamics and investment strategies. Through a qualitative approach, the research identifies declining consumer purchasing power as a key challenge affecting the profitability of the consumer and retail sectors and increasing market volatility. However, there are opportunities for investors through diversification into sectors that are more resilient to policy changes, such as technology and healthcare. The research also underscores the importance of more in-depth fundamental analysis to assess the impact of the VAT increase on projected corporate earnings. On the other hand, the government's efforts in maintaining economic stability through subsidies and effective policy communication are key to the successful implementation of this policy. The results of this study are expected to assist investors in devising adaptive strategies to deal with fiscal policy changes and capitalize on emerging long-term opportunities.